Analisis Faktor-Faktor Yang Mempengaruhi Laba Perusahaan Asuransi Umum Unit Usaha Syariah di Indonesia - Dwi Ayu Fitrianty; Fatmi Hadiani; Setiawan Setiawan; Hendra Sanjaya Kusno (Journal of Applied Islamic Economics and Finance, 2022)
Sharia business unit general insurance companies in 2017-2018 experienced a decline in performance. The decline in profits experienced must be known and what factors influence it. This study aims to analyze the effect of premium income, Risk-Based Capital, underwriting results, claim expenses, and operating costs on the profits of general insurance companies of sharia business units in Indonesia for the 2015-2020 period. This study uses panel data regression analysis with a quantitative approach using the Eviews 9 data processing application. Data were collected using the documentation method (secondary data) of 10 general insurance companies and Islamic business units in Indonesia registered with the OJK from 2015 to 2020. The results showed that simultaneously premium income, Risk-Based Capital, underwriting results, claims expenses, and operating costs had a significant effect on profits. Partially, premium income has a negative and significant effect on profit, while Risk-Based Capital, claims expense, and operating costs have a positive and significant effect on profit. Then the underwriting results have no significant effect on profits.